Pemberdayaan Masyarakat dalam Meningkatkan Kemandirian Ekonomi Melalui Program Usaha Mikro di Desa Maninjau - Shelvi Arma Yudha; Fazwa Maura Zacky; Riki Fernando Helmi; Yulia Hanoselina; Rahmadhona Fitri Helmi (CV. ITTC INDONESIA, 2025)
Community empowerment is a strategic approach to increasing economic independence, especially in rural areas. This study aims to analyze the impact of micro-enterprise programs on increasing economic independence of the community in Maninjau Village, West Sumatra. The method used is a descriptive qualitative approach with interview techniques, field observation, and documentation. The results of the study indicate that the implementation of micro-enterprise training programs such as entrepreneurship, capital assistance, and business assistance can encourage the growth of new business units managed by the local community, especially by women and village youth. A significant impact can be seen from the increase in family income, expansion of local economic networks, and increased knowledge and entrepreneurial skills. However, challenges such as limited market access, low financial literacy, and program desires are still challenges that need to be overcome. Overall, this empowerment program shows great potential in changing the pattern of economic independence into a more independent and sustainable pattern. This study recommends the need for synergy between local governments, financial institutions, and local assistants in strengthening the micro- enterprise ecosystem in the village.